Does Economic Insecurity Reduce all Types of Expenditures? - Anthony Lepinteur; Rémi Yin (Global Labor Organization (GLO), 2022)
The prudence theory predicts that economic insecurity reduces all consumption expenditures. We question this prediction by estimating the effect of economic insecurity on various expenditure items using an Australian longitudinal data set (HILDA) and panel regressions. Our results confirm that total consumption declines in response to greater economic insecurity and that this decline is greater for those with high risk aversion. However, we observe a clear gradient related to the degree of necessity of goods and services: the more necessary the consumption items, the weaker the effect of insecurity.
Keywords: D11; D12; E21; 330; Household expenditures; Economic insecurity; Prudence